(untitled) (Research, Society and Development, 2025)
Objective: to characterize the epidemiological profile of mortality and hospital morbidity due to neoplasms in the Southeast region in the 2021-2022 biennium. Methods: This is a retrospective and quantitative epidemiological study, with data from the Mortality Information System (SIM) and the Hospital Information System (SIH), available in DATASUS in the years 2021 and 2022. Results: Recorded 213,462 deaths from neoplasms, with an increase of 3.1%, the majority of deaths occurred in males (51%), in people self-declared as white (53%) and aged between 60-79 (52.4%). There was an increase in the number of female deaths (4.5%), as well as people aged between 60 and 79 years (4.1%) and people declared black (5.1%). The primary cause with the highest incidence was lung cancer, with 26,214 deaths, and the state of São Paulo had the highest percentage of deaths with 52.8%. Hospitalizations exceeded 500 thousand, with an average stay of 5.4 days, totaling an expense of around R1.2 billion reais in the two-year period. Conclusion: It was verified through this study that neoplasms in the southeast region represent a growing problem, reflected in high rates of mortality and hospital morbidity.